Insulin resistance and adverse metabolic profile in overweight/obese and normal weight of young women with polycystic ovary syndrome - Maryam Gholinezhad; Masoumeh Golsorkhtabaramiri; Sedighe Esmaeilzadeh; Azita Ghanbarpour (Babol University of Medical Sciences, 2018)
Background: Polycystic ovary syndrome (PCOs) is an endocrine-metabolic disorder. This study intends to determine the comparison of insulin resistance (IR) and metabolic disturbance in overweight/obese and normal-weight of young women with polycystic ovary syndrome. Methods: Using a comparative cross-sectional study design in 2015, 27 normal weight (18<bmi Results: 112 women with PCOS participated in this study. The mean age was 22.4±3.48 years in the normal PCOS group (n=27) and 24.4±5.06 years in the overweight/obese PCOS patients (n=85). BMI had a significant straight correlation with insulin resistance (p<0.001) and a negative correlation with insulin sensitivity (p<0.001). BMI showed a straight stronger correlation with triglyceride (TG) (p<0.001) and LDL cholesterol (<0.05) and a stronger reverse relationship with SHBG (p<0.001). In overweight/obese group, 91.7% (48) of the women showed insulin resistance (HOMA>3.15) vs. 8.3% (5) in the normal group (P<0.001). 82.4% (62) of the overweight/obese group revealed low insulin sensitivity (QUICKI<0.34) while this value was 17.6 % (13) within their lean counterparts (p<0.001). In the study group, 89.7 % (54) showed elevated fasting insulin concentration (>13µU/ml) vs. 10.3% (7) in the control group (p<0.001). Conclusions: Overweight/obese PCOs patients revealed higher insulin resistance and lower insulin sensitivity, and also greater TG and LDL cholesterol. Priority of management of insulin resistance and lipid profile should be considered on identifying these potentially major complications.</bmi